Measurement and evaluation of pesticide residue risk in vegetables: evidence from China - Li, Taiping; Jiang, Xiaoshan; Qiu, Menghui (Frontiers in Public Health, 2025)
IntroductionWith the modernization of agricultural production and the widespread use of chemical pesticides, pesticide residue risk has emerged as a significant public health concern globally. Pesticide residues in vegetables represent a potential hazard to consumer health. A scientific evaluation of their risk status not only enhances information transparency but also provides a precise foundation for food safety regulation.MethodsThis study devised a vegetable pesticide residue risk index by integrating the probability of residue detection and the extent of associated harm, utilizing 294,703 monitored sampling data across 30 provinces from 2021 to 2023 to methodically assess and quantify the risk of vegetable pesticide residues in China.ResultsOut of 52 vegetable types analyzed, 33 had pesticide residue levels that surpassed the permissible limits, with leeks and celery registering the highest risk indices. Regarding regional variations, Jiangsu, Jilin, Hubei, Hainan, and Heilongjiang were identified with the highest risk levels, while Ningxia, Yunnan, Shaanxi, Gansu, and Tianjin presented the lowest. The dispersion of vegetable pesticide residues has been progressively extending from the northeast towards the southwest. The predominant pesticide residues were found in three types—Clothianidin, Procymidone, and Chlorpyrifos, which constituted 43.6% of the overall exceedances.DiscussionThese findings provide a scientific basis for risk-based regulation, supporting region-specific inspection and targeted pesticide control. The study advocates tailored regulatory measures that consider both regional risk profiles and pesticide characteristics to reduce residue risks. Enhanced data transparency further empowers consumers to make informed choices, fostering a bottom-up compliance mechanism.